Contemporary Practice of Natural Science Training in Higher Education Institutions in Poland, Hungary and the Czech Republic: Neurobiological Aspects of Psychology - Pshenychna, Natalia; Bilyk, Valentyna; Honcharuk, Vitalii; Rozhi, Inna; Vasylenko, Kateryna (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2022)
The article examines the program principles and subject content of natural science training of future psychologists in Central Europe (Poland, Hungary and the Czech Republic). The choice of these countries for the study is due to the fact that despite short period of membership in the European Union, the countries achieved a significant progress in developing national education systems. The purpose of the article is to identify the main trends in natural science training of future psychologists and their correlation with the latest ideas of neurobiology, which is gradually becoming complementary to psychological, pedagogical and other humanities. Using methods of analysis (content analysis of educational programs; analysis of educational content for accordance with the latest advances in neurobiology), comparative method, statistical methods and extrapolation method, it was found that natural science training in universities in Poland, Hungary and the Czech Republic partially corresponds to practical application of neurobiology in the professional practice of psychologists. We present specific aspects of qualitative differences in the conclusions. We also calculated that the quantitative ratio of major subjects differs: the volume of credits for natural science training of future psychologists in the curricula of the analysed higher education institutions in Poland is about 6%, in the Czech Republic - 9-10%, and in Hungary - 11-12%.Theinternational significance of the article lies in identification of positive practical and formal approaches to neurobiological training, which requires organizational and methodological reforms of psychological education in Eastern Europe.
Keywords: Scope of education; interdisciplinary integration; study credits; practical training